TRANSPARANSI PENGELOLAAN ANGGARAN DAERAH: SEBUAH ALTERNATIF PEMBERANTASAN KORUPSI DI TINGKAT DAERAH - Hendrikus Triwibawanto Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
In this refrmation era, local government requires to be more and more transparentregarding its budget management. The transparent management of local budget toconstitutes a noble effort on the part of local government, especially when involving all local stakeholders in formulating the allocation and use of the budget. The absences of transparent budget mangement and involvement of local stakeholders weaken the implementation of local good governance. They may also trigger corruption practices. Such phenomena seem to have embeded among most local governments all over the country. Therefore, this article tries to reveal that trasparent management of local budget may become an alternative approach in diminishing corruption practices.